A Comparative Analysis of the Socio-Economic Challenges Faced by SMMEs: The Case of the Emfuleni and Midvaal Local Municipal Areas - Molefe, Karabo; Meyer, Natanya; de Jongh, Jacques (Journal of Economics and Behavioral Studies, 2018)
Flourishing and thriving small, medium and micro enterprise (SMME) sectors have become one of the leading recognised cornerstones of economic development. The ability of these businesses to act as key drivers of economic growth, innovation and job creation make them valuable assets towards any nation’s strive for a more inclusive economic and social outlook. For South Africa in particular, burdened by an epidemic of unemployment, poverty and income inequality, SMMEs role in improving the socio-economic environment proves pivotal. Yet, despite their potential, these businesses face a myriad of challenges, emanating from both internal and external environments, that restricts their growth and development. The primary aim of this study is to identify and compare the main socio-economic challenges faced by SMMEs in two local areas within the Vaal Triangle region. The study made use of a quantitative research approach and a cross-sectional research design through means of the survey method. The sample consisted of a total of 198 SMME owners that resided in both the Emfuleni (ELM) (n = 100) and Midvaal (MLM) (n = 98) local municipal areas. Data analysis involved the use of descriptive statistics, cross tabulations and chi-square tests. Overall the results of the study revealed that amongst the biggest challenges faced by SMMEs included managerial as well as economic aspects such as a lack of skilled labour, insufficient business training and lacklustre local economic conditions. The comparative analysis further revealed more significant infrastructural challenges in the Emfuleni local municipal area while market challenges such as a lack of demand as well as higher transportation costs were experienced by SMMEs located in the Midvaal area. The findings of the study provide valuable insight towards fostering an enabling environment for SMME development, specifically on local levels. In this regard policy stakeholders should adopt a multi-sectoral SMME focus. Possible recommendations include enhanced macroeconomic stability, strong public-private partnership formation and the provision of strong business support structures that facilitate management skills development together with the provision of strategic finance facilities.